2012
DOI: 10.1016/j.ajhg.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mutations in TMEM5 and ISPD as a Cause of Severe Cobblestone Lissencephaly

Abstract: Cobblestone lissencephaly is a peculiar brain malformation with characteristic radiological anomalies. It is defined as cortical dysplasia that results when neuroglial overmigration into the arachnoid space forms an extracortical layer that produces agyria and/or a "cobblestone" brain surface and ventricular enlargement. Cobblestone lissencephaly is pathognomonic of a continuum of autosomal-recessive diseases characterized by cerebral, ocular, and muscular deficits. These include Walker-Warburg syndrome, muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 52 publications
0
108
0
1
Order By: Relevance
“…Indeed, homozygous or biallelic mutations in the GPR56 ligand, COL3A1 were also recently found associated with a COB-like malformation [228]. Nevertheless, one third of the studied COB-LIS cases has not been genetically linked to any mutation and remain unexplained [215,218]. Non-genetic causes are still recognized for COB-LIS, including prenatal vascular problems and viral infections [43].…”
Section: A Type II Lissencephaly (Cobblestone)mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, homozygous or biallelic mutations in the GPR56 ligand, COL3A1 were also recently found associated with a COB-like malformation [228]. Nevertheless, one third of the studied COB-LIS cases has not been genetically linked to any mutation and remain unexplained [215,218]. Non-genetic causes are still recognized for COB-LIS, including prenatal vascular problems and viral infections [43].…”
Section: A Type II Lissencephaly (Cobblestone)mentioning
confidence: 99%
“…These genes include POMT1, POMT2, POMGNT1, FKTN, FKRP, LARGE, ISPD, GTDC2, TMEM5, POMK, B4GAT1, B3GALNT2 (see Table 4) [212,213,[215][216][217][218][219][220][221][222][223][224][225]. Other mutations are rare, described in only a few patients with WWS, and include genes encoding BM constituents, such as LAMB1, LAMC3 and COL4A1, and the transmembrane and tetratricopeptide repeat containing 3 gene, TMTC3 [215,218,226], coding for a protein for which its link is currently unclear.…”
Section: A Type II Lissencephaly (Cobblestone)mentioning
confidence: 99%
“…Omannosylation is an important step in glycosylation and is essential for the interaction of a-dystroglycan with extracellular matrix proteins, such as laminin-a2 [Cirak et al, 2013]. Six studies of the ISPD gene mutations in patients with cobblestone lissencephaly [Vuillaumier-Barrot et al, 2012], WWS [Czeschik et al, 2013;Roscioli et al, 2012;Willer et al, 2012] and congenital and limb-girdle muscular dystrophies [Baranello et al, 2015;Cirak et al, 2013] have been published, and multiple rare variants were found in 29 independent families. All affected individuals with homozygous segmental intragenic deletion of the ISPD gene exhibited progressive muscular dystrophy with a severe WWS phenotype, including hydrocephalus, cobblestone lissencephaly of the cerebral cortex, severe brainstem hypoplasia and hypoplasia of the cerebellum cases [Roscioli et al, 2012;Willer et al, 2012].…”
Section: Discussionmentioning
confidence: 98%
“…While the WWS phenotype of the affected individuals with ISPD mutations was described for postnatal cases [Cirak et al, 2013;Czeschik et al, 2013;Roscioli et al, 2012;Willer et al, 2012], only few prenatal cases were published [Vuillaumier-Barrot et al, 2012]. We report two prenatally detected ISPD gene deletions in foetuses with multiple brain anomalies that corresponded to the WWS phenotype.…”
Section: Introductionmentioning
confidence: 86%
“…Récemment, il a été montré que la synthèse du CDP-Ribitol ( Figure 1E), substrat pour FKRP et FKTN, est catalysée par une enzyme codée par le gène ISPD [9,45]. Ce gène avait été identifié par différentes équipes dès 2013, à partir d'études sur des patients LISII [28] ou WWS [46,47]. Des mutations du gène ISPD avaient ensuite également été identifiées chez des patients avec une clinique moins sévère, parfois sans atteinte neurologique, à l'image de ce qui est constaté pour les patients FKRP.…”
Section: Gènes Candidatsunclassified